Between Equality and the Right to Be Different—The Politicization of Concepts in the Fight against Discrimination Due to Sexual Orientation - Costa, Bruno (2021)
The debate around the principle of equality and the theme of discrimination around sexual orientation has been one of the most relevant in the process of ensuring the spread of human rights. After ensuring a set of civil and political rights, several groups and social movements have warned political actors of the need to look at each citizen’s individuality and guarantee through legislation and daily practices, respect for that individuality. This process is being conducted around the dichotomy between the concepts of equality and difference. It is from this analysis of the two concepts that we come across the theme of the rights of the lesbian, gay, bisexual, transvestite, transexual and transgender (LGBTQ+) community. With a qualitative approach, and while referring to the historical path of this theme, we review the central concepts in the promotion of equality and analyze the dichotomy between equality and difference. We ask, in an increasingly globalized world, does it make sense to point out difference as a mechanism for the defense of equality? Using semiotics, we approach the two central concepts and the political effort to normalize this theme to the public, using the Portuguese case (law and Non-Governmental organizations action) to characterize the central debate on equality and difference.